Marka Hłaski gry z popkulturą - Kunz, Tomasz (Załącznik Kulturoznawczy, 2024)
Marek Hłasko was the first Polish writer who so consciously and on such a large scale referred in his work to motifs, plot patterns and conventions taken from popular culture, primarily from cinema and cheap pulp fiction. These borrowings, which gained particular importance in his quasi-autobiographical works – Piękni dwudziestoletni (en. Beautiful Twentysomethings) and Listy z Ameryki (en. Letters from America) – could have made him the first Polish postmodernist writer. However, Hłasko lacked distance to the conventions he imitated in his stories and instead of using them to expose the artificiality of his characters' linguistic behaviors, he tried to use them to re-enchant the world or express the truth of his own inner experience, falling into the trap of sentimentalism often masked by ostentatious cynicism.